PEMBERIAN GANTI RUGI YANG LAYAK DALAM KAITANNYA DENGAN PENATAAN SEKTOR INFORMAL DI KOTA SURABAYA - Dwi Tatak Subagiyo (Perspektif, 2002)
The purpose of research on the subject is to give a description of informal sector in a way to get proper compensation of their relocation as a consequence of urban development policy. Regulations of land affairs, such as the right of authorizing the land, lay out and landscape arrangement and the compensation rule have been set, but sometimes it does not work as expected. The worker’s reason to refuse the relocation is that strategic and high economical value of the present location.